2014
DOI: 10.1136/gutjnl-2013-306069
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide insufflation improves the intubation depth and total enteroscopy rate in single-balloon enteroscopy: a randomised, controlled, double-blind trial

Abstract: ClinicalTrial.gov identifier: NCT01758900.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 16 publications
3
52
1
5
Order By: Relevance
“…Thus, as recommended by a previous study [16], we employed carbon dioxide (CO 2 ) insufflation to reduce post-procedure pain and bowel distention. Intriguingly, previous studies have shown that CO 2 insufflation can even improve the intubation depth and total endoscopy rate of SBE [16,17]. Hence, it will also be interesting to examine the effect of CO 2 insufflation on the efficacy and safety of DBE and SBE in the future.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, as recommended by a previous study [16], we employed carbon dioxide (CO 2 ) insufflation to reduce post-procedure pain and bowel distention. Intriguingly, previous studies have shown that CO 2 insufflation can even improve the intubation depth and total endoscopy rate of SBE [16,17]. Hence, it will also be interesting to examine the effect of CO 2 insufflation on the efficacy and safety of DBE and SBE in the future.…”
Section: Discussionmentioning
confidence: 97%
“…6 Li et al reported there was no significant difference between CO 2 group and air group. 8 The different anesthesia approaches might have contributed to the discrepancy. Pooling the results only reached statistical significance at 1 h after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Hirai et al 6 performed arterial blood gas analysis, and Li et al 8 recorded end-tidal CO 2 after balloon-assisted Figure 2. Forest plot displaying the weighted mean difference (WMD) and 95% confidence intervals (95% CIs) of each study for the intubation depth of oral enteroscopy.…”
Section: Co 2 Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auch für die Single-Ballon-Enteroskopie konnten neben einer Schmerzreduktion verbesserte Intubationstiefen gezeigt werden -bei Li et al im Mittel ca. 90 cm von oral und anal[28,29]. In der Studie unserer Arbeitsgruppe zeigte sich die verbesserte Eindringtiefe v. a. bei voroperierten Patienten -im Mittel ca.…”
unclassified